Tantangan Dan Prospek Akuntansi Syariah di Era Globalisasi - Gunawan Aji; Robiatul Adawiyyah; Ivanka Khoirunnisa; Salsabila, Cintia; Ratnawati Ratnawati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Sharia accounting faces significant challenges in the era of globalization, including integration with international standards, technological adaptation, and emphasis on sustainability and responsible finance. However, Islamic accounting also offers the opportunity to become an ethical and sustainable financial model, with principles such as the prohibition of investments that are environmentally or socially damaging. To develop these financial practices, inter-institutional collaboration, increasing sharia financial literacy, and developing better standards are needed. Thus, sharia accounting can strengthen its position in the global economy and help build a more just and sustainable society.